On Some Immature Girls and their Destinies: Narrating Girlhood in Josip Barković’s Novel Alma - POŽGAJ, Petra (Anafora, 2023)
By engaging the debates on feminist postclassical narratology and by approaching literary representations of girls as one of the sites of the production of girlhood, understood as a category independent of concrete discursive articulations and not as a reflection of a stable biological or social category, this paper focuses on the analysis of Josip Barković’s Alma and aims to contribute to discussions on the relationship between gender and narration. Specifically, it argues that gender must not be considered in isolation or, in other words, that ignoring the broader socio-cultural context while discussing novels about Yugoslav girls would mean ignoring the significance of Yugoslav socialism and attributing a feminist impulse to Barković’s novel. A brief discussion of the theoretical and socio-cultural context allows for the analysis of Barković’s novel focused on the narrative fashioning of girlhood and the figure of the girl in order to show that a consideration of the context of the novel and its further existence in the cultural field provides a twofold advantage. On the one hand, it broadens the understanding of the actual cultural representations of the figure of youth with their incredibly important role in the Yugoslav socialist society while taking into account the category of gender. On the other hand, it expands the understanding of the socio-cultural context in which that figure is produced.